Translating the Spanish Economic Discourse of the Crisis: Dealing with the Inevitability of English Loanwords - Orts Llopis, María Ángeles; Almela Sánchez-Lafuente, Ángela (International Journal of English Studies, 2009)
Our current study aims at analysing and describing the plethora of English loans in the Spanish discourse of economy -in the shape of direct or indirect borrowings- as a result of the swift changes taking place in the course of the present Global Systemic Crisis. The need for precision and accurateness in the deployment of technical terms, or terms of art, in the Spanish discourse of Economics has triggered our scrutiny of an ad hoc corpus of economic news-items from a range of digital periodicals in the field of finance and economics. With the aid of three financial bilingual glossaries intended for the specialized Spanish-speaking community, and the deployment of a specific taxonomy on linguistic incorporations, we have developed a system of lexical selection, reuniting, analyzing and explaining a representative group of real data illustrating, somehow, the neologistic borrowing process during the above-mentioned financial havoc. Further, our study attempts to enlighten and facilitate the translator’s task when dealing with the economic language in Spanish and the English loans incorporated just before, during, and after the critical period under scrutiny.